2020
DOI: 10.1109/access.2020.3007098
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Scope Creep on Project Success: An Empirical Investigation

Abstract: Advocates of software engineering and software project management stated in the literature that creeping of scope is one of the most common causes for the failure of software projects. Also, advocates believed that it could occur in almost every software project, which leads to compromise in quality, delayed schedules, increase cost and decreased customer satisfaction. However, the lack of empirical evidence demands a comprehensive investigation to identify the factors of scope creep and to propose a conceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 53 publications
0
24
0
1
Order By: Relevance
“…A properly characterized and managed scope prompts transmit a quality product in agreed cost and intimate determined time schedules. According to Chaos Report from Standish Group, 51% of IT ventures are "tested"genuinely late, over the financial plan, and anticipated deficient highlights [6]. Figure 1 presents the statistics regarding project failures due to scope creep.…”
Section: Research Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…A properly characterized and managed scope prompts transmit a quality product in agreed cost and intimate determined time schedules. According to Chaos Report from Standish Group, 51% of IT ventures are "tested"genuinely late, over the financial plan, and anticipated deficient highlights [6]. Figure 1 presents the statistics regarding project failures due to scope creep.…”
Section: Research Motivationmentioning
confidence: 99%
“…Some of the researchers considered these pillars as a triangle of the whole project because these multi-dimensional aspects provide coverage to the overall project. Hence, scope creep factors would be increased in case of an issue in any area [6]. Through the conducted systematic review, scope creep factors are identified from the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The survey statistics showed that 21% of the software projects failed, often termed aborted or canceled, and 53% were challenged, completed but with time and budget overrun, also with fewer features and functions. Among several causes of software project failures, an inadequate scope is deemed as one of the biggest contributors [4], [9], [16], [17], [32], [35], [57], [65]. It has been recognized that an inadequate or incomplete scope definition at the early stages of the project life cycle is a common source of difficulties in the implementation process [4], [6], [16], [34], [35], [43].…”
Section: A Role Of Scope In Project Successmentioning
confidence: 99%
“…Consequently, a poorly defined project scope imposes a variety of adverse effects on the project schedule, cost, and quality [4], [15]. It has been found that incomplete or poor scope definition extends the project time and efforts, disrupts project rhythm, and lowers the morale of the project team [4], [6], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation